The paradox of information : greenhorn reality / Nur Afifa Khairuddin and Wan Siti Nur Atieqah Wan Hanudin - Khairuddin, Nur Afifa; Wan Hanudin, Wan Siti Nur Atieqah (Faculty of Information Management, 2015)
The issues of unemployed graduates are very concern and serious issues. This issue can no longer be ignored as unemployed youngster will cause problem to family and country. The unemployment is very crucial issues that will always haunt the new and fresh graduates. The problem of getting a suitable job is getting serious each day. Many of the greenhorns will face the same problem. This article will be focusing on the reasons as why this situation occurs. Primarily the reasons came from the graduates themselves and also from the company or the organization that will became their employer. This article also will include the step and action to overcome the problem.